Determination of traits responding to iron toxicity stress at different stages and genome-wide association analysis for iron toxicity tolerance in rice (Oryza sativa L.) - Theerawitaya, Cattarin; Wanchana, Samart; Ruanjaichon, Vinitchan; Tisaram, Rujira; Samphumphuang, Thapanee; Sotesaritkul, Thanyaporn; Cha-um, Suriyan; Toojinda, Theerayut (Frontiers in Plant Science, 2022)
Rice is the staple food for more than half of the world’s population. Iron toxicity limits rice production in several regions of the world. Breeding Fe-tolerant rice varieties is an excellent approach to address the problem of Fe toxicity. Rice responds differently to Fe toxicity at different stages. Most QTLs associated with Fe toxicity have been identified at the seedling stage, and there are very few studies on Fe toxicity across different stages. In this study, we investigated agro-morphological and physiological traits in response to Fe toxicity in a rice diversity panel at seedling, vegetative, and reproductive stages and applied GWAS to identify QTLs/genes associated with these traits. Among agro-morphological and physiological parameters, leaf bronzing score (LBS) is a key parameter for determining Fe toxicity response at all stages, and SDW could be a promising parameter at the seedling stage. A total of 29 QTLs were identified on ten chromosomes. Among them, three colocalized QTLs were identified on chromosome 5, 6, and 11. Several QTLs identified in this study overlapped with previously identified QTLs from bi-parental QTL mapping and association mapping. Two genes previously reported to be associated with iron homeostasis were identified, i.e., LOC_Os01g72370 (OsIRO2, OsbHLH056) and LOC_Os04g38570 (OsABCB14). In addition, based on gene-based haplotype analysis, LOC_Os05g16670 was identified as a candidate gene for the colocalized QTL on chromosome 5 and LOC_Os11g18320 was identified as a candidate gene for the colocalized QTL on chromosome 11. The QTLs and candidate genes identified in this study could be useful for rice breeding programs for Fe toxicity tolerance.